Organism-Dependent Fungicidal Activities of Azoles - Manavathu, Elias K. (American Society for Microbiology, 1998)
We investigated the antifungal activities of itraconazole and voriconazole on Aspergillus species by time kill studies, and the results were compared with those obtained for Candida species. Exposure of Aspergillus fumigatus conidia to varying concentrations (1.25 to 10 μg/ml) of itraconazole and voriconazole resulted in cellular death; the cytocidal effect was time and concentration dependent. In contrast, no killing of Candida albicans occurred in the presence of itraconazole and voriconazole at concentrations as high as 10 μg/ml, although candidal growth was inhibited compared to the drug-free control. Amphotericin B (1.25 to 10 μg/ml), on the other hand, killed both A. fumigatus and C. albicans. Similar results were obtained for non-A. fumigatus aspergilli and non-C. albicans Candida species. These observations indicate that both itraconazole and voriconazole are cytocidal agents for Aspergillus species but not for Candida species, suggesting that azoles possess organism-dependent fungicidal activities.